News Production Management of CekFakta in Dealing with Hoax Outbreak Information on the Social Media - Benni Indo; Anang Sujoko (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2023)
In the digital era, the competition of mass media leads to the practice of media economy as well as creativity in presenting news content. On the other hand, the mass media are challenged to deal with hoaxes. This study aims to find out how the management of news production at Tempo through the CekFakta page. This study uses qualitative methods with content analysis data collection techniques and in-depth interviews. Data collection through interviews with CekFakta journalists, article documentation and literature studies since 2021. The results of this study reveal that there are three important aspects that determine news products, namely the format, quality and content leverage. In terms of format, the news on the CekFakta page has a specificity conclusion the information circulating is true or not. There are three charts that make up the body of fact-checking news, first introduction to the viral information, secondly an explanation of the method of finding the truth of the information and the third stage is conclusions related to the information being studied. Consumer can understand easily the content of the information with the guide. In terms of quality, Tempo has a methodology that becomes the basic guideline for journalists to make news. The benefit aspect is done by disseminating the news through social media. In practice, to achieve these three aspects, fact-checking journalists work with the help of tools obtained through collaboration with external participants. In the era of media industrialization, the news agency has become a company that aims to make a profit. News, as a product of mass media companies must also be designed in such a way as to generate profits. Thus, the practice of journalism must also be adapted to the times. Fact-checking journalism exists not only to improve the quality of information, but also to bring financial benefits to the company.